2020
DOI: 10.3390/jcm9030797
|View full text |Cite
|
Sign up to set email alerts
|

Individual Responsiveness to Physical Exercise Intervention in Acutely Hospitalized Older Adults

Abstract: We analyzed inter-individual variability in response to exercise among acutely hospitalized oldest-old adults. In this ancillary analysis of a randomized controlled trial, 268 patients (mean age 88 years) were assigned to a control (n = 125, usual care) or intervention group (n = 143, supervised exercise, i.e., walking and rising from a chair [1–3 sessions/day]). Intervention group patients were categorized as responders, non-responders, or adverse responders (improved, no change, or impaired function in activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…In addition, a recent randomized controlled trial suggests that implementing an in-hospital intervention, including individualized and supervised (by rehabilitation professional) moderate-intensity resistance, balance and walking exercises (two 20-minute daily sessions), statistically and clinically improved functional capacities (SPPB; (13)) and muscle function (power and strength; (14)). Another study, which implemented simple supervised exercises (walking, sit-to-stand) during weekdays, highlighted that only 10% of participants decreased their ADL levels (15,16). Finally, we recently demonstrated that implementing simple unsupervised exercises in a short geriatric unit was not only feasible and acceptable (17), but also an efficient way to improve a patient's functional capacity, increase nonsedentary physical activity and reduce the burden on healthcare (i.e.…”
mentioning
confidence: 84%
“…In addition, a recent randomized controlled trial suggests that implementing an in-hospital intervention, including individualized and supervised (by rehabilitation professional) moderate-intensity resistance, balance and walking exercises (two 20-minute daily sessions), statistically and clinically improved functional capacities (SPPB; (13)) and muscle function (power and strength; (14)). Another study, which implemented simple supervised exercises (walking, sit-to-stand) during weekdays, highlighted that only 10% of participants decreased their ADL levels (15,16). Finally, we recently demonstrated that implementing simple unsupervised exercises in a short geriatric unit was not only feasible and acceptable (17), but also an efficient way to improve a patient's functional capacity, increase nonsedentary physical activity and reduce the burden on healthcare (i.e.…”
mentioning
confidence: 84%
“…), severe disability (e.g., bed rest conditions, cachexia conditions, neurological disorders, etc. ), adverse or blunted response to exercise, and low adherence ( Seynnes et al, 2004 ; Rivera-Torres et al, 2019 ; Lalande et al, 2020 ; Valenzuela et al, 2020b ). In addition, many sarcopenic patients may not meet the minimum criteria for exercise recommendations according to recent guidelines ( Fragala et al, 2019 ; Izquierdo et al, 2021b ).…”
Section: Does Exercise Prevent or Revert Sarcopenia? Evidence And Lim...mentioning
confidence: 99%
“…Of these, 236 study full-texts were reviewed and 16 publications met eligibility criteria. Two publications were completed on the same study sample (Ortiz-Alonso et al, 2020;Valenzuela et al, 2020) Abbreviations: GFSA, gutter frame with supplemental air; GFSO, gutter frame with supplemental oxygen; LOS, length of stay; NA, not applicable; NR, not reported; RCT, randomized controlled trial; RSA, rollator with supplemental air; RSO, rollator with supplemental oxygen. a Denotes studies that could be used in meta-analysis for hospital length of stay.…”
Section: Re Sultsmentioning
confidence: 99%